Effects of light on plant regeneration - Sithu, Lin (2014)
Plants have the capacity to regenerate new shoot apical meristems in vitro, but the regeneration rates can vary greatly. Light is a essential environmental factor that could affect plant regeneration. Varying light conditions are known to affect regeneration, but the optimal conditions of light have yet to be determined. By utilizing Arabidopsis seeds with the temporal-inducible ectopic expression of WUSCHEL line (35S>>WUS), de novo shoot regeneration was stimulated under varying light intensities, wavelengths and photoperiods. High light intensities (60-76 µmol m-2 s-1) were found to be most beneficial with respect to shoot regeneration, with a periodic light/dark cycle showing an increase in regeneration frequency over constant light conditions of the same light intensity. The absence of light on the other hand, showed the most reduction in regeneration events. Exclusive exposure to blue light (470nm) showed higher regeneration frequencies than red light (636nm). Regeneration events were shown to be coordinated by the requirement of multiple factors that work alone or in tandem. Furthermore, the better understanding of environmental factors such as wavelength requirements could see potential integration into commercial development of environmental growth plant breeding chambers that are highly optimized for crop breeding.